2014
DOI: 10.1167/iovs.14-15075
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Contour Changes Following Surgery for Idiopathic Epiretinal Membrane

Abstract: We developed a novel foveal contour grading method to assess retinal contour in ERM eyes before and after surgery. In eyes with ERM and no foveal depression, the majority did not regain foveal depression following surgery even though retinal thickness improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
(37 reference statements)
2
23
0
Order By: Relevance
“…We used the total retinal thickness (TRT) changes in a study of 117 patients with ERM following ERM peeling, 5 and another study on 41 patients with idiopathic ERM following ERM and ILM peeling for sample calculations. 6 Based on these studies, the mean TRT change was set as 94 (±54) μm. We found that a sample size of 4 patients was required to detect a difference with a significance level of 0.05 and a power of 80%.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…We used the total retinal thickness (TRT) changes in a study of 117 patients with ERM following ERM peeling, 5 and another study on 41 patients with idiopathic ERM following ERM and ILM peeling for sample calculations. 6 Based on these studies, the mean TRT change was set as 94 (±54) μm. We found that a sample size of 4 patients was required to detect a difference with a significance level of 0.05 and a power of 80%.…”
Section: Sample Sizementioning
confidence: 99%
“…3 Following ERM removal surgery, further disturbances in retinal microstructure frequently develop such as alterations in foveal contour, inner retinal dimpling, and thinning or thickening of retinal areas. [4][5][6][7][8] Several attempts have been made to ascertain the nature of retinal morphological changes following surgery, using various methods. 5,6,9 Most focused on one specific aspect such as foveal contour or total retinal thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several classifications for iERM exist according to different standards [1720]. Only a few of them classified iERM based on a clinical scale or optical coherence tomography (OCT) finding [21].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] This decrease in the thickness has been documented by optical coherence tomography (OCT) as a recovery of retinal thickening. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Earlier studies 20,21 showed that this decrease continued for 24 months; however, it was not determined whether the decrease will continue for longer times.…”
mentioning
confidence: 99%